The Strategy of Flouting Maxim by the Characters of The Little Mermaid Movie in “Live Action Version” - Eka Sarinah Napitupulu; Arsen Nahum Pasaribu; Rotua Elfrida Pangaribuan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The purpose of this study is to find out the types and the strategies of flouting maxim in The Little Mermaid movie. This study uses the qualitative descriptive method. The theory used in this study based on Grice (1989) cooperative principle theories and the strategy flouting maxims based on Grundy (2002). It presents the two objectives in the study, namely, the types of flouting maxims and the strategy that are used to flout the maxim performed by the characters and conversation from the movie. The results show that all types strategies and flouted maxim are found in the movie, that are frequency of types flouting maxim flouting maxim quantity is 12 (44.44%), flouting maxim quality is 4 (14.81%), flouting maxim relevance is 7 (25.92%) flouting maxim manner is 4 (14.81%), and the most dominant flout maxim is the flouting the maxim of quantity is 12 (44.44%) utterances. All the types strategy flouting maxims are found in the movie, the strategy of understatement is the most frequently used to flouts the maxim of quantity with its appearance 10 times out of 27 data. The second strategy being obscure with appearance 7 times. The third strategy metaphor and changing the topic have the same frequency 3 times. The last one strategy overstatement and irony have the same frequency 2 times. It was also found the implied meaning behind main characters' linguistic maxims depending on the context of conversation. It is hoped that this study can provide benefits in terms of practically, for the English department students, lecturers, readers, and researchers.